2010
DOI: 10.1074/jbc.c110.166066
|View full text |Cite
|
Sign up to set email alerts
|

Collapsin Response Mediator Protein-2 (Crmp2) Regulates Trafficking by Linking Endocytic Regulatory Proteins to Dynein Motors

Abstract: Endocytosis is a conserved cellular process in which nutrients, lipids, and receptors are internalized and transported to early endosomes, where they are sorted and either channeled to degradative pathways or recycled to the plasma membrane. MICAL-L1 and EHD1 are important regulatory proteins that control key endocytic transport steps. However, the precise mechanisms by which they mediate transport, and particularly the mode by which they connect to motor proteins, have remained enigmatic. Here we have identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 41 publications
1
63
0
Order By: Relevance
“…These findings suggest that CRMP1 mediates Sema3A-induced retrograde axonal transport. It has been reported that CRMP2 is involved in kinesin-1-dependent transport of the Sra1-WAVE1 complex (Arimura et al, 2009) and in regulation of trafficking by linking endocytic regulatory proteins to dynein motors (Rahajeng et al, 2010). CRMP2 has been reported to be able to directly bind to voltage-dependent Na + channels, modulating the channel's slow inactivation (Dustrude et al, 2013;Wang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that CRMP1 mediates Sema3A-induced retrograde axonal transport. It has been reported that CRMP2 is involved in kinesin-1-dependent transport of the Sra1-WAVE1 complex (Arimura et al, 2009) and in regulation of trafficking by linking endocytic regulatory proteins to dynein motors (Rahajeng et al, 2010). CRMP2 has been reported to be able to directly bind to voltage-dependent Na + channels, modulating the channel's slow inactivation (Dustrude et al, 2013;Wang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The CH and LIM domains of MICAL-L1 bind to CRMP2 (60). On the other hand, the LIM domain of MICAL-L2 interacts with F-actin and promotes F-actin crosslinking (60).…”
Section: Lim Domainmentioning
confidence: 99%
“…Collectively, these data demonstrated that HTLV-1 infection, possibly through Tax activity, profoundly altered posttranslational processing of CRMP2, resulting in more active molecular form in T lymphocyte and elevated migration as a consequence. Tax and CRMP2 colocalized at uropod and cell-cell contact in HTLV-1-infected T cells Given 1) the crucial role of CRMP2 in remodeling neural cell and T lymphocyte cytoskeleton by direct binding to microtubules (25,44) and also in participation, as a cargo receptor, in the transport of specific vesicles (45,46), 2) the ability of Tax protein to modulate CRMP2 activity in infected lymphocyte, in particular cytoskeleton binding (shown in this paper), 3) the capacity of infected cell to transfer Tax though a well organized cell-cell contact (the so-called virological synapse (47), and 4) the role of microtubule in T cell signaling (48), we suspected CRMP2 to bind Tax protein at specific sites in lymphocyte cytoplasm to cooperate. Preliminary analyses using immunoprecipitation and CRMP2-GST pull-down strategy were unable to detect a direct association between these proteins.…”
Section: Htlv-1 Acts On Crmp2 Proteolytic Processing Favoring the Prmentioning
confidence: 99%